Arterial disorders : definition, clinical manifestations, mechanisms and therapeutic approaches - Berbari, Adel; Mancia, Giuseppe (Springer International Publishing Imprint: Springer, 2015)
As our knowledge about arterial disease is greatly expanding, the aim of this book is to explore all aspects of arterial pathology, including classification, clinical manifestations, pathogenesis, and therapeutic options. The discussion of pathophysiologic mechanisms of arterial disease is wide ranging, encompassing hemodynamic, metabolic, humoral, inflammatory, genetic and environmental factors. Particular emphasis is placed on recent concepts, such as: the role of age-associated arterial alterations in the initiation and progression of cardiovascular diseases in older persons, the importance of mineral metabolism-bone vascular interactions, the clinical and prognostic significance of the renal resistive index, retinal circulation, toxemia of pregnancy as an arterial disease, and the role of pulmonary/vascular interaction in pulmonary hypertension and cross-talk of macrocirculation and microcirculation in target organ involvement. Evaluation procedures are carefully explained, and the full range of currently available therapeutic options, including lifestyle modifications and pharmacologic approaches, are described and appraised.